The interaction between parental behavior and motivations to drink alcohol in high school students. (3rd May 2020) - Voce, Alexandra; Anderson, Kristen G.
ABSTRACT: Background: Alcohol use during adolescence has been predicted by motives to drink or abstain, as well as parental attitudes to youth drinking. As peers can provide access and opportunities to drink, permissiveness of peers' parents toward alcohol is also of importance. Objectives: We examined whether adolescent alcohol use is predicted by motives to drink or abstain, strictness of one's own parents, alcohol permissiveness by peers' parents, and an interaction between these factors. Method: A sample of high school students from the Pacific Northwest ( N = 1056; 49% girls; m age = 15.6) completed alcohol use and parenting measures, the Drinking Motives Questionnaire-Revised, and the Motives for Abstaining from Alcohol Questionnaire. A zero-inflated negative binomial regression model examined the combined influence of motives, parent's strictness, and peer's parents' permissiveness on past month use. Results: Parental permissiveness was associated with higher rates of drinking among students with low (but not high) conformity motives and motives to abstain. Higher parental permissiveness was associated with higher rates of drinking among students with low (but not high) coping motives. Conclusions: Our results demonstrate that parental strictness regarding teen alcohol use extends beyond the family unit to influence adolescent drinking in the broader social network. Parents may have a limited capacity to deter drinking through setting rules and expectations for adolescents who are motived to drink to conform but such limit setting maybe particularly helpful for youth with fewer motives to abstain.